Peran Dukungan Sosial dari Sudut Pandang Teman Sebaya terhadap Dewasa Awal yang Melakukan NSSI - Edo, Eureka Nathania; Arianti, Rudangta (Universitas Muhammadiyah Metro, 2025)
This study aims to understand the role of social support provided by early adult individuals to peers who commit non-suicidal self-injury (NSSI). The method used is a qualitative approach with in-depth interviews with two early adult participants who provide social support to friends who experience NSSI. The results showed that the social support provided included emotional, instrumental, informational, and social network dimensions, which were influenced by the quality of the relationship, motivation for providing support, and consistency in monitoring the friend's condition. This study provides important implications for the development of social and psychological interventions to support individuals with NSSI behaviors, although this study is limited to certain age groups and genders, so further research is needed to expand understanding.